Estudo dos efeitos antifúngico e citotóxico da curcumina na presença de antioxidantes - LUDWIG, DANIEL BRUSTOLIN (2013)
The curcumin, a polyphenol extracted from the plant Curcuma longa is a compound of great relevance in the treatment and prevention of various diseases due to their biological properties such as antioxidant, anti-inflammatory and antitumoral. The antifungal effect on various types of strains, is another activity associated with curcumin. The curcumin degradation is strongly when using neutral pH to basics, which can be minimized with the addition of substances with antioxidant properties, such as ascorbic acid, glutathione and N-acetylcysteine. With this, the aim of this work is to evaluate the antifungal and cytotoxic effect of curcumin in the absence or in the presence of antioxidant ascorbic acid, glutathione and N-acetylcysteine. The results showed that curcumin associated with antioxidants against the strains of Candida spp and Cryptococcus spp showed pronounced complementary effect due to the reduction in the growth of the strains evaluated by counting colonies, but some clinical strains and one ATCC strain of Candida spp not show this effect. Curcumin and antioxidants, by testing normal cells (erythrocytes), showed no cytotoxic effect at the concentrations tested. Tests on tumor cell line, HEp-2 and HRT-18, evaluated by MTT method and the cell morphology, demonstrated an increased effect of curcumin with the combination of ascorbic acid. Protection was also observed in the degradation of curcumin in physiological medium by applying light emitting diode in the presence of antioxidants. It is concluded that curcumin in the presence of antioxidants as glutathione, N-acetylcysteine and ascorbic acid have increased stability in physiological media demonstrating a complementary effect of these substances, thus ensuring an increase in cytotoxic and antifungal activity curcumin.